Train passengers' perceptions and preferences for different platform and carriage design features - Jie Yang; Nirajan Shiwakoti; Richard Tay (Journal of Public Transportation, 2024)
Specific design features and functions on the platform and inside of the train carriage can significantly affect how efficiently and smoothly passengers can move in and out of the train. Industry follows the design standard and guidelines to satisfy the minimum requirement. However, the views of rail users are often overlooked and not well understood. This study fills the knowledge gap by investigating different platform and train carriage design features and understanding train passengers' perceptions and preferences for the proposed design. An online passenger survey targeting Melbourne Metro train users was conducted. By analyzing 429 valid responses, we gained insights into passengers' perceptions and preferences regarding train and platform design. A novel finding is that a vertical pole is the most preferred handhold type, while a rigid handrail is the least preferred handhold type. The 2+2 seating is voted as the most preferred interior layout, which is consistent with previous studies. The ranking on 2+2 seating layout is moderately associated with travel time and travel frequency, while the ranking on 2+3 seating is strongly associated with travel time. It is also found that the preferences for boarding sign and occupancy sign design are significantly associated with gender, age group, and travel frequency. Surprisingly, no statistically significant associations were found between any of the personal or travel variables with queuing sign preference, side seating ranking, or hanging strips ranking. The findings drawn from the analysis and the recommendation of this paper can provide valuable guidance for rail manufacturers in implementing design changes, as well as for service operators in adopting new strategies and interventions to enhance service quality and customer satisfaction.